The role of knowledge, sustainable consumption promotion, and consumption intention for sustainable consumption behavior - Muslimah, Lili; Muhyidin, Ayi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The millennial generation plays a crucial role in making consumer decisions and has significant potential to drive the transformation towards more sustainable consumption patterns. This study aims to investigate the extent to which environmental knowledge and sustainable consumption promotion affect the intention and behavior of sustainable consumption among millennials. To test this framework, we conducted a quantitative research approach by administering an online survey to collect data from 155 millennial respondents. We utilized Structural Equation Modeling to test the proposed hypotheses. The findings of this research indicate that the level of environmental knowledge and sustainable consumption promotion have a significant influence on millennials' intention to adopt sustainable consumption behaviors, which in turn impact actual actions in sustainable consumption. The findings of this research provide valuable insights into how elements such as knowledge and promotion can act as drivers or barriers for millennials in adopting more sustainable consumption patterns. The implications of these findings have great potential in shaping the foundation of more effective strategies and campaigns to encourage sustainable consumption behavior among millennials, while also increasing awareness of pressing environmental issues.